Interaction between plasma homocysteine and the MTHFR C.677C > T polymorphism is associated with site‐specific changes in DNA methylation in humans. Issue 1 (6th August 2018) - Nash, Alexander J.; Mandaviya, Pooja R.; Dib, Marie-Joe; Uitterlinden, André G.; van Meurs, Joyce; Heil, Sandra G.; Andrew, Toby; Ahmadi, Kourosh R.
ABSTRACT: One‐carbon metabolism provides a direct link among dietary folate/vitamin B12 exposure, the activity of the enzyme methylenetetrahydrofolate reductase (MTHFR), and epigenetic regulation of the genome via DNA methylation. Previously, it has been shown that the common C.677C > T polymorphism in MTHFR influences global DNA methylation status through a direct interaction with folate status and (indirectly) with total homocysteine (tHcy) levels. To build on that and other more recent observations that have further highlighted associations among MTHFR C.677C > T, tHcy, and aberrations in DNA methylation, we investigated whether the interaction between mildly elevated plasma tHcy and the C.677C > T polymorphism is associated with site‐specific changes in DNA methylation in humans. We used data on plasma tHcy levels, c.677C> T polymorphism, and site‐specific DNA methylation levels for a total of 915 white women and 335 men from the TwinsUK registry ( n = 610) and the Rotterdam study ( n = 670). We performed methylome‐wide association analyses in each cohort to model the interaction between levels of tHcy and C.677C > T genotypes on DNA methylation β values. Our meta‐analysis identified 13 probes significantly associated with rs1801133 × tHcy levels [false‐discovery rate (FDR) < 0.05]. The most significant associations were with a cluster of probes at the AGTRAP–MTHFR–NPPA/B gene locus on chromosome 1 (FDR = 1.3E–04), with additional probes on chromosomes 2, 3, 4, 7, 12, 16, and 19. Our top 2 hits on chromosome 1 were functionally associated with variability in expression of the TNF receptor superfamily member 8 ( TNFRSF8 ) gene/locus on that chromosome. This is the first study, to our knowledge, to provide a direct link between perturbations in 1‐carbon metabolism, through an interaction of tHcy and the activity of MTHFR enzyme on epigenetic regulation of the genome via DNA methylation.—Nash, A. J., Mandaviya, P. R., Dib, M.‐J., Uitterlinden, A. G., van Meurs, J., Heil, S. G., Andrew, T., Ahmadi, K. R. Interaction between plasma homocysteine and the MTHFR c.677C>T polymorphism is associated with site‐specific changes in DNA methylation in humans. FASEB J. 33, 833–843 (2019). www.fasebj.org